A method of welding a silicon carbide material
Patent Information
- Application Number
- CN202611460400.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
然而,SiC固有的高硬度、高熔点和低自扩散系数,使得通过传统机械加工制备大型或复杂形状构件极为困难且成本高昂
(1)连接性能卓越:原位生成的β-FeSi2连接层与SiC基体化学相容性好,界面结合强度高;接头具有优异的高温强度、抗氧化性和长期热稳定性,长期使用温度可达1000~1100℃。
Smart Images

Figure CN122977859A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of advanced ceramic material joining technology, and more particularly to a welding method for silicon carbide materials. Background Technology
[0002] Silicon carbide (SiC) ceramics and their composites (such as C / SiC) have become indispensable key materials in cutting-edge fields such as aerospace, nuclear energy (e.g., fusion reactor blankets and accident-tolerant fuel CLAD), and high-temperature thermal protection systems due to their excellent high-temperature strength, high thermal conductivity, good thermal shock resistance, and outstanding oxidation and corrosion resistance. However, the inherent high hardness, high melting point, and low self-diffusion coefficient of SiC make it extremely difficult and costly to fabricate large or complex-shaped components using traditional machining methods. Therefore, developing reliable and efficient SiC joining technologies is the only feasible way to integrate small, simple SiC components into large, complex functional parts. Summary of the Invention
[0003] In view of this, the object of the present invention is to provide a welding method for silicon carbide materials. The method provided by the present invention achieves effective bonding of silicon carbide materials, and the resulting weld joint has excellent high-temperature strength, oxidation resistance, and long-term thermal stability.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a welding method for silicon carbide materials, comprising the following steps: The surface of the silicon carbide material to be welded is pretreated to obtain pretreated silicon carbide material; the free silicon content of the silicon carbide material is greater than or equal to 10 wt%. A transition layer is applied to the surface of the pretreated silicon carbide material to be welded, and then annealing is performed to obtain a silicon carbide material with an intermediate layer attached. After assembling the silicon carbide material with the intermediate layer attached in a contact manner, heat treatment is performed to achieve welding of the silicon carbide material; The transition layer is either a first transition layer or a second transition layer; The first transition layer is a periodically stacked silicon-iron layer, which is a stacked silicon layer and an iron layer, and the iron layer is in contact with the silicon carbide material; The second transition layer is an iron thin film, which has an open porous structure or a vertical columnar crystal structure.
[0005] Preferably, when the free silicon content of the silicon carbide material is less than 10 wt%, the method further includes: applying a silicon-rich layer to the surface of the pretreated silicon carbide material to be welded, and then applying a transition layer; The silicon-rich layer is a polycrystalline Si layer, an amorphous silicon layer, or a Si-SiC hybrid layer; the free silicon content in the silicon-rich layer is greater than or equal to 90 wt%. The thickness of the silicon-rich layer is 5~50μm.
[0006] Preferably, the total thickness of the first transition layer is 0.4~2μm, and in the first transition layer, the thickness of the single silicon layer is 5~8nm, and the thickness of the single iron layer is 4~8nm; the thickness of the single silicon layer is greater than the thickness of the single iron layer.
[0007] Preferably, the single-layer silicon layer is applied by magnetron sputtering, and the magnetron sputtering parameters of the single-layer silicon layer include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working gas pressure is 0.5~1.0Pa, sputtering power is 150~400W, substrate temperature is 200~400℃, deposition time is 15~90s, target-substrate distance is 60~100mm; The single-layer iron layer is applied by magnetron sputtering, and the magnetron sputtering parameters of the single-layer iron layer include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working gas pressure is 0.3~0.8Pa, sputtering power is 100~300W, substrate temperature is 200~400℃, deposition time is 5~60s, target-substrate distance is 60~100mm.
[0008] Preferably, the total thickness of the second transition layer is 5~100μm; The second transition layer is applied by magnetron sputtering; When the second transition layer is an iron thin film with an open porous structure, the magnetron sputtering parameters include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working gas pressure is 1.0~2.5Pa, sputtering power is 80~200W, substrate bias voltage is 0V or -20~-50V, substrate temperature is 25~100℃, deposition rate is 0.5~2nm / s, target-substrate distance is 60~100mm. When the second transition layer is an iron thin film with a vertical columnar crystal structure, the magnetron sputtering parameters include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working pressure is 3.0~5.0 Pa, sputtering power is 80~200 W, substrate bias is 0 V or -20~-50 V, substrate temperature is 25~100 ℃, deposition rate is 0.5~2 nm / s, and target-substrate distance is 60~100 mm.
[0009] Preferably, the annealing temperature is 500~700℃, the holding time is 15~60min, and the vacuum degree of the annealing process is 1×10⁻⁶. -1 ~9×10 -1 Pa.
[0010] Preferably, the heating process of the heat treatment includes sequentially performing a first stage, a second stage, a third stage, and a fourth stage; The first stage is: heating to a first temperature at a first heating rate and holding for a first time; the first stage is carried out under the condition of introducing a protective gas; The second stage is: heating from the first temperature to the second temperature at a second heating rate and then holding for a second time; The third stage is: cooling down from the second temperature to the third temperature at a first cooling rate and then holding the temperature for the third time. The fourth stage is: cooling from the third temperature to the fourth temperature at a second cooling rate; The atmosphere in the second and third stages is a protective gas.
[0011] Preferably, the first heating rate is 25~35℃ / min, the first temperature is 500~600℃, and the first holding time is 2~10min; The second heating rate is 100~300℃ / min, the second temperature is 1130~1170℃, and the second holding time is 10~30min; The first cooling rate is 15~20℃ / min, the third temperature is 910~930℃, and the third holding time is 30~60min; The second cooling rate is less than or equal to 50℃ / min, and the fourth temperature is 300~400℃.
[0012] Preferably, the pretreatment includes machining.
[0013] Preferably, when the size of the silicon carbide material is greater than 1m, the heat treatment is performed in a laser welding torch, the laser welding torch comprising: Welding torch body: The welding torch body has a hollow cavity for introducing shielding gas; the hollow cavity is surrounded by an annular cavity for introducing cross-blowing gas; the hollow cavity is surrounded by a water-cooling jacket. A flexible sealing skirt is attached to the head of the welding torch body; A multi-channel gas supply system, comprising a protective gas supply system, a cross-blowing gas supply system, and a displacement gas supply system; the protective gas supply system is connected to the hollow cavity, the cross-blowing gas supply system is connected to the annular cavity, and the displacement gas supply system is connected to both the hollow cavity and the annular cavity.
[0014] This invention provides a welding method for silicon carbide materials.
[0015] This invention utilizes the reaction between free silicon in silicon carbide material and iron (Fe) in the transition layer to generate β-disilicide (β-FeSi2), thereby achieving a high-strength, high-temperature resistant connection between SiC components.
[0016] The beneficial effects of this invention are: (1) Excellent connection performance: The β-FeSi2 connecting layer generated in situ has good chemical compatibility with the SiC matrix and high interfacial bonding strength; the joint has excellent high temperature strength, oxidation resistance and long-term thermal stability, and the long-term service temperature can reach 1000~1100℃.
[0017] (2) Strong applicability: The method of the present invention is applicable to the joining of different types of SiC (RBSC, SSiC, C / SiC composite materials) and the process is highly adjustable.
[0018] Furthermore, the heat treatment heating procedure includes sequentially performing a first stage, a second stage, a third stage, and a fourth stage. This invention combines the Fe in the transition layer with the heat treatment process, shortening the traditional β-FeSi2 formation process, which requires tens or even hundreds of hours, to within a few hours, achieving rapid reaction sintering and high process efficiency.
[0019] Furthermore, when the size of the silicon carbide material is greater than 1m, the heat treatment is performed in a welding torch. The welding torch of this invention enables localized protective gas oxidation-resistant welding of large components, as well as highly reliable welding technology for ceramic and metal dissimilar materials; it overcomes the limitation that large components must rely on vacuum or atmosphere-protected furnaces, realizing on-site, flexible welding and greatly expanding the engineering application scope of this technology. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the welding torch of the present invention; Figure 2 The XRD pattern of the welded joint obtained in Example 1; Figure 3 The image shows a surface SEM image of the iron thin film with a vertical columnar crystal structure obtained in Example 2. Figure 4 Here is a cross-sectional SEM image of the welded joint obtained in Example 2; Figure 5The XRD pattern of the welded joint obtained in Example 2; Figure 6 Here is a surface SEM image of the iron thin film with an open porous structure obtained in Example 3; Reference numerals: 1-flexible sealing skirt, 2-hollow cavity, 3-annular cavity, 4-water cooling jacket. Detailed Implementation
[0021] This invention provides a welding method for silicon carbide materials, comprising the following steps: The surface of the silicon carbide material to be welded is pretreated to obtain pretreated silicon carbide material; the free silicon content of the silicon carbide material is greater than or equal to 10 wt%. A transition layer is applied to the surface of the pretreated silicon carbide material to be welded, and then annealing is performed to obtain a silicon carbide material with an intermediate layer attached. After assembling the silicon carbide material with the intermediate layer attached in a contact manner, heat treatment is performed to achieve welding of the silicon carbide material; The transition layer is either a first transition layer or a second transition layer; The first transition layer is a periodically arranged silicon-iron layer, which is a silicon layer and an iron layer stacked together, and the iron layer is in contact with the silicon carbide material; The second transition layer is an iron thin film, which has an open porous structure or a vertical columnar crystal structure.
[0022] Unless otherwise specified, the raw materials used in this invention are preferably commercially available products.
[0023] The present invention pre-treats the surface of silicon carbide material to be welded to obtain pre-treated silicon carbide material; the free silicon content of the silicon carbide material is greater than or equal to 10 wt%.
[0024] In this invention, the silicon carbide material is preferably a reaction-sintered silicon carbide material or a sintered silicon carbide material.
[0025] In this invention, the preferred method for preparing the reaction-bonded silicon carbide material (RBSC / RBSiC) includes the following steps: mixing silicon carbide powder and a carbon source, molding the mixture to obtain a carbon blank; subjecting the carbon blank to a first sintering to obtain a sintered carbon blank; immersing the carbon blank in liquid silicon to obtain an impregnated carbon blank; and subjecting the impregnated carbon blank to a second sintering to obtain the reaction-bonded silicon carbide material. In this invention, the carbon source preferably includes one or more of carbon black, graphite, phenolic resin, and pitch; the mass ratio of silicon carbide powder to carbon source is preferably 1:0.5 to 1:2, specifically preferably 1:0.5, 1:1, 1:1.5, or 1:2. In this invention, the first sintering temperature is preferably 1000 to 1200°C, and the time is preferably 1 to 3 hours; the first sintering enables the polymeric carbon source phenolic resin or pitch in the carbon source to decompose into carbon and release volatiles. In this invention, the liquid silicon preferably comprises pure silicon melt, silicon-iron alloy melt, or silicon-chromium alloy melt; the iron content in the silicon-iron alloy melt is preferably 5-15% by mass; the chromium content in the silicon-chromium alloy melt is preferably 5-15% by mass; the impregnation temperature is preferably room temperature, and the time is preferably 30-120 min. In this invention, the second sintering temperature is preferably 1450-1750℃, and the holding time is preferably 1-3 h; the second sintering is preferably carried out under vacuum or a protective atmosphere; during the second sintering process, the liquid silicon penetrates into the porous sintered carbon blank under capillary force; the liquid silicon reacts with carbon to generate β-SiC, and the residual silicon fills the pores to achieve densification. After the second sintering, this invention preferably further includes: post-treatment of the obtained second sintered product. This invention does not specifically limit the operation of the post-treatment, as long as it can remove residual silicon or silicon alloy on the surface.
[0026] In this invention, the preferred method for preparing the sintered silicon carbide material includes the following steps: mixing α-SiC powder, a sintering aid, and a binder, and then sequentially molding and sintering to obtain the sintered silicon carbide material. In this invention, the sintering temperature is preferably 1900~2100℃, specifically preferably 1900℃, 1950℃, 2000℃, 2050℃, or 2100℃; the pressure is preferably 20~40MPa, specifically preferably 20MPa, 25MPa, 30MPa, 35MPa, or 40MPa; and the holding time is preferably 1~2 hours.
[0027] In this invention, the pretreatment preferably includes machining. The machining method is preferably grinding or etching. The workpiece used for grinding is a diamond grinding wheel, and the grit size of the diamond grinding wheel is preferably greater than or equal to 200 mesh, more preferably 400-1000 mesh, and specifically preferably 400 mesh. The etching method is preferably laser etching; the etching preferably forms an array pattern, the array pattern is preferably a microgroove array, the width of the microgrooves is preferably 5-8 μm, the aspect ratio is preferably 2-3, and the distance between the center lines of two adjacent microgrooves is preferably 15-25 μm, more preferably 20 μm. The machining amount is preferably 0.05-0.3 mm; after machining, the surface roughness (Ra) of the machined surface is preferably 0.1-1.0 μm, specifically preferably 0.5 μm. In this invention, the machining can obtain a fresh, flat surface with a certain roughness, increasing the bonding area.
[0028] In this invention, the free silicon content of the silicon carbide material is greater than or equal to 10 wt%. After the pretreatment, the invention preferably further includes sequential cleaning (referred to as the first cleaning) and vacuum degassing. In this invention, the first cleaning preferably includes sequential acetone ultrasonic cleaning and anhydrous ethanol ultrasonic cleaning; the acetone ultrasonic cleaning time is preferably 15-30 min, and the anhydrous ethanol ultrasonic cleaning time is preferably 15-30 min. After the first cleaning and before the vacuum degassing, the invention preferably includes drying, and the gas used for drying is preferably high-purity nitrogen or dry air. In this invention, the cleaning can remove oil stains and particulate matter. In this invention, the vacuum degassing temperature is preferably 1000-1200℃, the holding time is preferably 30-60 min, and the vacuum degree is preferably ≤1×10⁻⁶. -2 Pa, specifically preferably 5.0 × 10 Pa. -3 Pa. In this invention, the vacuum degassing treatment is preferably carried out in a vacuum furnace. The specific process of the vacuum degassing treatment in this invention is preferably as follows: the cleaned silicon carbide material is placed in a vacuum furnace for processing. In this invention, the vacuum degassing treatment can further remove adsorbed gases and impurities from the surface, purify the surface, and prepare for subsequent processing.
[0029] In this invention, when the free silicon content of the silicon carbide material is less than 10 wt%, it preferably further includes: applying a silicon-rich layer to the welding surface of the pretreated silicon carbide material, followed by the subsequent application of a transition layer. In this invention, the silicon-rich layer is preferably a polycrystalline Si layer, an amorphous silicon layer, or a Si-SiC hybrid layer. In this invention, the free silicon content in the silicon-rich layer is preferably greater than or equal to 90 wt%. In this invention, the thickness of the silicon-rich layer is preferably 5~50 μm.
[0030] In this invention, the preferred method for preparing the silicon-rich layer is plasma-enhanced chemical vapor deposition (PECVD), chemical vapor deposition (CVD), slurry coating sintering, or vapor phase silicon infiltration (VI).
[0031] In this invention, when the silicon-rich layer is preferably a polycrystalline Si layer, the preparation method of the polycrystalline Si layer is preferably low-pressure chemical vapor deposition (LPCVD). The LPCVD parameters of the polycrystalline Si layer include: the reaction gas is preferably SiH4, the deposition temperature is preferably 600~650℃, the deposition pressure is preferably 20~50Pa, and the deposition time is preferably 30~120min.
[0032] In this invention, when the silicon-rich layer is preferably an amorphous silicon layer, the preparation method of the amorphous silicon layer is preferably PECVD. The PECVD deposition parameters of the amorphous silicon layer include: the substrate temperature is preferably 250~350℃, more preferably 300℃; the working gas is preferably SiH4, and the flow rate of the SiH4 is preferably 40~60 sccm, more preferably 50 sccm; the radio frequency power is preferably 80~120W, more preferably 100W; and the deposition time is preferably 50~70min, more preferably 60min.
[0033] In this invention, when the silicon-rich layer is preferably a Si-SiC hybrid layer, the preparation method of the Si-SiC hybrid layer is preferably magnetron sputtering co-deposition, and the magnetron sputtering co-deposition parameters of the Si-SiC hybrid layer include: a background vacuum degree preferably ≤5.0×10⁻⁶. -4 The preferred working gas is argon, with a working pressure of 0.5–1.0 Pa. The preferred sputtering power for the silicon target is 150–300 W, and for the silicon carbide target it is 100–200 W. The substrate temperature is 300–500 °C, and the deposition time is 60–180 min. In this invention, the power supplies for both the silicon and silicon carbide targets are turned on simultaneously for sputtering. Silicon atoms (Si) and silicon carbide molecules / atomic groups (SiC) sputtered from both target surfaces are simultaneously deposited on the substrate surface, mixing at the microscale to form a "Si-SiC hybrid layer". By independently adjusting the sputtering power of the silicon and silicon carbide targets, the ratio of silicon to silicon carbide in the hybrid layer can be precisely controlled, thereby obtaining the target free silicon content (≥12 wt%). Co-deposition avoids the existence of multilayer film interfaces, forming a uniform nanoscale composite structure. The relatively high substrate temperature (300–500 °C) during deposition is conducive to atomic diffusion and enhances the bonding between the hybrid layer and the silicon carbide substrate.
[0034] After applying the silicon-rich layer, the present invention preferably further includes cleaning (referred to as second cleaning) and drying. The second cleaning is preferably ultrasonic cleaning with anhydrous ethanol, which can remove loose particles on the surface. The drying is preferably nitrogen drying.
[0035] This invention cleverly utilizes the large amount of free Si or silicon-rich layer contained in silicon carbide material as a reactant, avoiding the problems of uneven dispersion and contamination caused by the addition of silicon powder.
[0036] After obtaining the pretreated silicon carbide material, the present invention applies a transition layer to the surface of the pretreated silicon carbide material to be welded and performs annealing treatment to obtain silicon carbide material with an intermediate layer attached.
[0037] In this invention, the transition layer is either a first transition layer or a second transition layer. In this invention, the first transition layer is a periodically stacked silicon-iron layer, wherein the silicon-iron layer is a stacked silicon layer and an iron layer, and the iron layer is in contact with the silicon carbide material. In this invention, the total thickness of the first transition layer is preferably 0.4~2μm, specifically preferably 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, or 2μm. In this invention, the thickness of the single-layer silicon layer in the first transition layer is preferably 5-8 nm, specifically 5 nm, 6 nm, 7 nm, or 8 nm; the thickness of the single-layer iron layer is preferably 4-8 nm, specifically 4 nm, 5 nm, 6 nm, or 7 nm; the thickness of the single-layer silicon layer is greater than the thickness of the single-layer iron layer. In this invention, the single-layer silicon layer is applied by magnetron sputtering, and the magnetron sputtering parameters of the single-layer silicon layer include: a base vacuum preferably less than or equal to 5.0 × 10⁻⁶. -4 Pa, specifically preferably 3.0 × 10 Pa. -4 Pa; the working gas is preferably argon, the purity of which is preferably 99.999%, and the working pressure is preferably 0.5~1.0 Pa, specifically 0.5 Pa, 0.6 Pa, 0.7 Pa, 0.8 Pa, 0.9 Pa or 1.0 Pa; the sputtering power is preferably 150~400 W, specifically 150 W, 200 W, 250 W, 300 W, 350 W or 400 W; the substrate temperature is preferably 200~400℃, specifically 200℃, 250℃, 300℃, 350℃ or 400℃; the deposition time is preferably 15~90 s, specifically 15 s, 16 s, 20 s, 30 s, 45 s, 60 s, 75 s or 90 s; the target-substrate distance is preferably 60~100 mm, specifically 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 85 mm, 90 mm, 95 mm or 100 mm.
[0038] In this invention, the preferred method for applying the monolayer iron layer is magnetron sputtering, and the magnetron sputtering parameters for the monolayer iron layer include: a background vacuum level preferably less than or equal to 5.0 × 10⁻⁶. -4 Pa, specifically preferably 3.0 × 10 Pa. -4 Pa; the working gas is preferably argon, the purity of which is preferably 99.999%, and the working pressure is preferably 0.3~0.8 Pa, specifically 0.3 Pa, 0.4 Pa, 0.5 Pa, 0.6 Pa, 0.7 Pa or 0.8 Pa; the sputtering power is preferably 100~300 W, specifically 100 W, 150 W, 200 W, 250 W or 300 W; the substrate temperature is preferably 200~400℃, specifically 200℃, 250℃, 300℃, 350℃ or 400℃; the deposition time is preferably 5~60 s, specifically 5 s, 7.5 s, 10 s, 20 s, 30 s, 40 s, 50 s or 60 s; the target-substrate distance is preferably 60~100 mm, specifically 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 85 mm, 90 mm, 95 mm or 100 mm.
[0039] In this invention, controlling the substrate temperature to 200~400℃ during the deposition of monolayer silicon and monolayer iron helps to improve the film density and interfacial adhesion.
[0040] In this invention, the first transition layer is a nanolayered structure with alternating light and dark areas, which can provide a large number of interfaces in subsequent reactions, allowing Fe and Si atoms to be pre-mixed at the nanoscale. This results in a shorter reaction path, greatly reducing the formation temperature of β-FeSi2 and shortening the reaction time. The formation temperature of the β phase can be reduced by more than 150°C.
[0041] In this invention, the second transition layer is an iron thin film, which has an open porous structure or a vertical columnar crystal structure. The total thickness of the second transition layer is preferably 5-100 μm, specifically preferably 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, or 100 μm. The film density of the second transition layer is 60-85% of the theoretical value, and it contains interconnected pores.
[0042] In this invention, the second transition layer is preferably applied by magnetron sputtering.
[0043] In this invention, when the iron thin film has an open porous structure, the magnetron sputtering parameters of the second transition layer include: the base vacuum is preferably less than or equal to 5.0 × 10⁻⁶. -4The working gas is preferably argon, with a purity of 99.999%, and the working pressure is preferably 1.0~2.5 Pa, specifically 1.0 Pa, 1.5 Pa, 2.0 Pa, or 2.5 Pa; the sputtering power is preferably 80~200 W, specifically 80 W, 100 W, 120 W, 140 W, 150 W, 160 W, 170 W, 180 W, 190 W, or 200 W; the substrate bias is preferably 0 V or -20~-50 V, specifically 0 V, -20 V, or -25 V. -30V, -35V, -40V, -45V or -50V; the substrate temperature is preferably 25~100℃, specifically preferably 25℃, 40℃, 60℃, 80℃ or 100℃; the deposition rate is preferably 0.5~2nm / s, specifically preferably 0.5nm / s, 1nm / s, 1.5nm / s or 2nm / s; the target-substrate distance is preferably 60~100mm, specifically preferably 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm or 100mm.
[0044] In this invention, when the iron thin film has a vertical columnar crystal structure, the magnetron sputtering parameters of the second transition layer include: the base vacuum is preferably less than or equal to 5.0 × 10⁻⁶. -4 The working gas is preferably argon, with a purity of 99.999%, and the working pressure is preferably 3.0~5.0 Pa, specifically 3.0 Pa, 3.5 Pa, 4.0 Pa, 4.5 Pa, or 5.0 Pa; the sputtering power is preferably 80~200 W, specifically 80 W, 100 W, 120 W, 140 W, 150 W, 160 W, 170 W, 180 W, 190 W, or 200 W; the substrate bias is preferably 0 V or -20~-50 V, specifically 0 V, -20 V, - 25V, -30V, -35V, -40V, -45V or -50V; the substrate temperature is preferably 25~100℃, specifically preferably 25℃, 40℃, 60℃, 80℃ or 100℃; the deposition rate is preferably 0.5~2nm / s, specifically preferably 0.5nm / s, 1nm / s, 1.5nm / s or 2nm / s; the target-substrate distance is preferably 60~100mm, specifically preferably 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm or 100mm.
[0045] In this invention, the porous structure of the second transition layer provides a channel for Si diffusion, which is conducive to the rapid diffusion of Si atoms from the substrate to the interior of the film, and thus facilitates the rapid formation of β-FeSi2; the gaps between the columnar crystals can serve as diffusion channels to alleviate volume change stress.
[0046] In this invention, the annealing temperature is preferably 500~700℃, specifically 500℃, 550℃, 600℃, 650℃ or 700℃; the holding time is preferably 15~60min, specifically 15min, 30min, 45min or 60min; the vacuum degree of the annealing process is preferably 1×10⁻⁶. -1 ~9×10 -1 Pa, specifically preferably 5.0 × 10 Pa. -1 Pa.
[0047] In this invention, the annealing treatment can stabilize the thin film structure of the transition layer, release internal stress, and promote the initial interdiffusion of Fe / Si.
[0048] The present invention obtains silicon carbide material with an attached intermediate layer. After assembling the silicon carbide material with the attached intermediate layer in a contact manner, it is subjected to heat treatment to achieve welding of silicon carbide material.
[0049] In this invention, after assembly and before heat treatment, it is preferable to further apply a pre-tightening force to the assembled parts. The pre-tightening force is preferably 0.1~0.5MPa, and more specifically 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa or 0.5MPa.
[0050] In this invention, the heating process of the heat treatment preferably includes performing a first stage, a second stage, a third stage, and a fourth stage in sequence; The first stage is: heating to a first temperature at a first heating rate and then holding for a first time; The second stage is: heating from the first temperature to the second temperature at a second heating rate and then holding for a second time; The third stage is: cooling down from the second temperature to the third temperature at a first cooling rate and then holding the temperature for the third time. The fourth stage is: cooling from the third temperature to the fourth temperature at a second cooling rate.
[0051] In this invention, the first stage is carried out under the condition of introducing a replacement gas, preferably nitrogen; in the first stage, the air in the system is replaced completely with nitrogen; the first heating rate is preferably 25~35℃ / min, more preferably 30℃ / min; the first temperature is preferably 500~600℃, specifically preferably 500℃, 550℃ or 600℃; the first holding time is preferably 2~10min, specifically preferably 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min.
[0052] In this invention, the atmosphere of the second stage is preferably a protective gas, which is preferably argon or helium; the flow rate of the protective gas is preferably 10~25 L / min, specifically 10 L / min, 15 L / min, 20 L / min or 25 L / min; the second heating rate is preferably 100~300℃ / min, specifically 100℃ / min, 150℃ / min, 200℃ / min, 250℃ / min or 300℃ / min; the second temperature is preferably 1130~1170℃, specifically 1130℃, 1140℃, 1150℃, 1160℃ or 1170℃; the second holding time is preferably 10~30 min, specifically 10 min, 15 min, 20 min, 25 min or 30 min. In this invention, the second stage preferably also introduces a cross-blowing gas, which preferably includes argon and / or helium; the flow rate of the cross-blowing gas is preferably 5~15 L / min, specifically 5 L / min, 8 L / min, 10 L / min or 15 L / min; the flow direction of the cross-blowing gas is preferably perpendicular to the flow direction of the protective gas; the cross-blowing gas forms an air curtain, dispersing welding plumes, assisting in isolating air, and protecting both sides of the weld. In this invention, in the second stage, the Fe film undergoes a solid-state diffusion reaction with Si in SiC, mainly forming one or more of the intermediate phases of η-Fe5Si3, ε-FeSi, α-FeSi2 and α-Fe2Si5.
[0053] In this invention, the atmosphere of the third stage is preferably the same as that of the second stage, and will not be repeated here; the first cooling rate is preferably 15~20℃ / min, specifically preferably 15℃ / min, 16℃ / min, 17℃ / min, 18℃ / min, 19℃ / min or 20℃ / min; the third temperature is preferably 910~930℃, specifically preferably 910℃, 920℃ or 930℃; the third holding time is preferably 30~60min, specifically preferably 45min. In this invention, the third stage involves a co-deposition / absorptivity reaction (ε-FeSi + α-Fe2Si5 → β-FeSi2), completing the final formation and densification of the β-FeSi2 bonding layer.
[0054] In this invention, the atmosphere of the fourth stage is preferably the same as that of the second stage, and will not be described again here; the second cooling rate is preferably less than or equal to 50°C / min, more preferably 20~50°C / min, and more preferably 30°C / min; the fourth temperature is preferably 300~400°C, and more preferably 300°C, 350°C or 400°C.
[0055] Following the fourth stage, the present invention preferably further includes natural cooling to room temperature. In this invention, the process of natural cooling to room temperature helps to reduce thermal stress.
[0056] In this invention, when the size of the silicon carbide material is less than or equal to 1m, the heat treatment is preferably carried out in a vacuum furnace.
[0057] In this invention, when the size of the silicon carbide material is greater than 1 m, the heat treatment is performed in a laser welding torch. Preferably, the laser welding torch is an improved version of an existing laser welding torch, with the improvement primarily involving gas path modification. The following description focuses only on the gas path improvements; other aspects not covered remain consistent with the existing laser welding structure.
[0058] In this invention, the laser welding gun includes: Welding torch body: The welding torch body has a hollow cavity 2, which is used to introduce shielding gas; the hollow cavity 2 is surrounded by an annular cavity 3, which is used to introduce cross-blowing gas; the hollow cavity 2 is surrounded by a water cooling jacket 4. Flexible sealing skirt 1, the flexible sealing skirt 1 being connected to the head of the welding torch body; A multi-channel gas supply system, comprising a protective gas supply system, a cross-blowing gas supply system, and a displacement gas supply system; the protective gas supply system is connected to the hollow cavity 2, the cross-blowing gas supply system is connected to the annular cavity 3, and the displacement gas supply system is connected to both the hollow cavity 2 and the annular cavity 3.
[0059] Figure 1 This is a schematic diagram of the laser welding gun of the present invention. The following is in conjunction with... Figure 1 Describe its structure.
[0060] In this invention, the laser welding torch includes a welding torch body, which has a hollow cavity 2 for introducing a protective gas; the hollow cavity 2 is surrounded by an annular cavity 3 for introducing a cross-blowing gas; the wall separating the hollow cavity 2 and the annular cavity 3 has an array of micropores; the array of micropores allows the cross-blowing gas to be blown into the hollow cavity 2; the hollow cavity 2 is surrounded by a water-cooling jacket 4; the water-cooling jacket 4 is used for cooling; the material of the welding torch body is preferably a high-temperature resistant alloy or water-cooled copper, and the high-temperature resistant alloy is preferably Inconel 600.
[0061] In this invention, the laser welding gun includes a flexible sealing skirt 1, which is connected to the head of the welding gun body; the material of the flexible sealing skirt 1 is preferably a multilayer high-temperature ceramic fiber fabric and an elastic high-temperature resistant silicone rubber composite material; the high-temperature ceramic fiber fabric is preferably alumina fiber; the flexible sealing skirt 1 can adapt to the surface morphology of the workpiece to achieve sliding sealing.
[0062] In this invention, the laser welding torch includes a multi-channel gas supply system, comprising a shielding gas supply system, a cross-blowing gas supply system, and a displacement gas supply system. The shielding gas supply system is connected to the hollow cavity 2, the cross-blowing gas supply system is connected to the annular cavity 3, and the displacement gas supply system is connected to both the hollow cavity 2 and the annular cavity 3. In this invention, the shielding gas supplied by the shielding gas supply system flows out through the hollow cavity 2 from the central hole of the welding torch body, covering the area directly above the molten pool / reaction zone. The shielding gas is argon or helium, with the purity of argon and helium independently ≥99.999% and a dew point ≤-70℃. In this invention, the cross-blowing gas supplied by the cross-blowing gas supply system is injected into the hollow cavity 2 through a micro-hole array in the annular cavity 3, forming an air curtain. The cross-blowing gas is mainly used to disperse plumes or volatiles that may be generated due to high temperatures during welding, preventing them from contaminating the lens or interfering with observation, and simultaneously providing auxiliary protection to both sides of the weld. In this invention, the displacement gas supply system is preferably an expandable soft enclosure; before welding begins, the displacement gas supply system temporarily encloses the area to be welded, and ambient displacement gas is introduced to replace the air within it, reducing the oxygen content of the welding environment to below 10 ppm. In this invention, the cross-blowing gas preferably includes argon and / or helium. In this invention, the displacement gas preferably includes nitrogen.
[0063] In this invention, the laser welding gun preferably further includes a heating system. The invention does not specifically limit the structure of the heating system; any existing laser welding gun heating system can be used. Specifically, the heating system can be located inside the welding gun body. The heating system can preferably be a high-power laser head, a focusing infrared lamp, or a small induction coil, more preferably a high-power laser head. The high-power laser head can preferably be a high-power fiber laser, with a wavelength preferably of 1070 nm. The high-power fiber laser, due to its concentrated energy and good controllability, easily achieves localized high-temperature reaction sintering.
[0064] In this invention, the laser welding torch preferably further includes a monitoring and feedback system. This invention does not specifically limit the monitoring and feedback system; existing monitoring and feedback systems for laser welding torches can be used. In this invention, the monitoring and feedback system may preferably include one or more of an integrated infrared thermometer, an integrated micro-spectrometer, and an oxygen sensor. The integrated infrared thermometer monitors the temperature of the reaction zone in real time, and the integrated micro-spectrometer or oxygen sensor monitors the oxygen content in the local microenvironment and provides feedback to the control system to adjust the gas flow rate and heating power.
[0065] The following detailed description of the welding method for silicon carbide materials provided by the present invention, in conjunction with embodiments, should not be construed as limiting the scope of protection of the present invention.
[0066] Example 1: Welding of SiC (RBSC) itself: Materials: Two pieces of reaction-bonded silicon carbide material (containing 15% free silicon), with dimensions of 50mm × 25mm × 5mm.
[0067] Pretreatment: The surface of the reaction-bonded silicon carbide material was ground to Ra 0.5 μm using a 400-mesh diamond grinding wheel, followed by ultrasonic cleaning with acetone and anhydrous ethanol for 15 min each, and then subjected to a 5.0 × 10⁻⁶ grit surface treatment. -3 Vacuum degassing treatment at 1200℃ for 30 minutes.
[0068] The first transition layer was prepared on two reaction-sintered silicon carbide materials respectively: iron layer, silicon layer, iron layer, silicon layer... iron layer and silicon layer were deposited sequentially according to the magnetron sputtering parameters in Table 1. A [Fe(6nm) / Si(8nm)]×100 nanometer multilayer film was deposited by magnetron sputtering, with a total thickness of about 1.4μm.
[0069] Table 1. Magnetron sputtering parameters of Example 1
[0070] Annealing: at 5.0×10 -1 Annealing at 600℃ for 30 minutes at Pa to obtain silicon carbide material with an attached intermediate layer.
[0071] After assembling the silicon carbide material with the intermediate layer attached in an interlayer contact manner, a slight preload (0.2 MPa) is applied.
[0072] Then Figure 1 The welding torch (heating system is a laser) undergoes heat treatment, and the specific process is as follows: First stage: The temperature is increased from room temperature to 600℃ at a rate of 30℃ / min and held for 3 minutes. During this process, high-purity nitrogen is introduced to replace the air in the system. After the first holding is completed, the protective gas (high-purity argon) and the cross-blowing gas (high-purity argon) are turned on and the flow rates are controlled at 15L / min and 8L / min, respectively.
[0073] Second stage: Then, the temperature is increased from 600℃ to 1150℃ at a rate of 300℃ / min and held for 15min. During this process, the flow rates of the protective gas (high-purity argon) and the cross-blowing gas (high-purity argon) are 15L / min and 8L / min, respectively. During this stage, the Fe / Si nanolayer film undergoes intense interdiffusion and reaction, forming intermediate phases such as ε-FeSi and α-Fe2Si5.
[0074] The third stage involves a first cooling rate of 15℃ / min from 1150℃ to 920℃ followed by a third holding period of 45min. During this process, the flow rates of the protective gas (high-purity argon) and the cross-blowing gas (high-purity argon) are 15L / min and 8L / min, respectively. This stage completes the transformation to the stable β-FeSi2 phase and grain growth (ε-FeSi+α-Fe2Si5→β-FeSi2), achieving densification of the connecting layer.
[0075] Fourth stage: Turn off the heater and cool down from 920℃ to 300℃ at a rate of 30℃ / min; Fifth stage: Then turn off the protective gas and cross-blowing gas, and allow it to cool naturally to room temperature.
[0076] To achieve the welding of silicon carbide materials.
[0077] Result: The weld was dense and there were no macroscopic cracks.
[0078] Figure 2 The XRD pattern of the welded joint. Figure 2 The result shows that β-FeSi2 was formed in the joint.
[0079] The room temperature three-point bending strength test of the welded joint, conducted according to GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", showed that the joint strength was 322 MPa, reaching 92% of the strength of the base material, and the fracture occurred in the base material rather than the weld.
[0080] After oxidizing in air at 1000℃ for 100 hours, the strength retention rate of the welded joint is >85%.
[0081] Example 2 Materials: Two pieces of sintered silicon carbide (SSiC) material, measuring 50mm × 25mm × 5mm. Typical characteristics include: predominantly α-SiC phase, density ≥ 3.10 g / cm³. 3It has a free silicon content of <0.5%, high hardness, and stable chemical properties.
[0082] Key challenge: SSiC contains almost no free silicon, making it impossible to directly provide a sufficient silicon source for the reaction. Traditional methods require the addition of large amounts of silicon powder or the use of extremely high temperatures, resulting in complex processes that can easily damage the substrate. The core of this embodiment is to create a high-throughput reaction diffusion path at a lower temperature by constructing a combination of a surface silicon source and a columnar porous iron film.
[0083] 1. Preprocessing: 1.1 Construction of silicon-rich layer on SiC interface surface: Since SSiC itself is silicon-deficient, the first step is to artificially construct a silicon-rich layer with high activity and high specific surface area on the interface surface.
[0084] Machining: A microgroove array is fabricated on the connecting surface using femtosecond laser surface texturing technology. The distance between the center lines of two adjacent microgrooves is 20μm, the width of the microgrooves is 6μm, the depth is 15μm, and the aspect ratio is 2.5. This treatment can increase the surface area and generate a large number of nanocrystalline and amorphous layers on the inner wall of the grooves, which can significantly improve the surface activity.
[0085] Deposition of silicon-rich layer: Plasma-enhanced chemical vapor deposition (PECVD) was used with SiH4 as the gas source to deposit an amorphous silicon (a-Si) thin film on the textured surface; deposition parameters: substrate temperature 300℃, SiH4 flow rate 50sccm, RF power 100W, deposition time 60min.
[0086] Results: An amorphous silicon film with a thickness of about 2 μm (free silicon content ≥99 wt%) was obtained. This film uniformly covered the microtextured surface and was firmly bonded to the activated SiC substrate, providing a sufficient and easily diffused silicon source for subsequent reactions.
[0087] 1.2 Cleaning: After depositing the amorphous silicon thin film, it is gently ultrasonically cleaned with anhydrous ethanol to remove loose particles on the surface, and then dried with nitrogen.
[0088] 2. Second transition layer: On the prepared silicon-rich layer surface, an iron thin film with a vertical columnar crystal structure is deposited.
[0089] Equipment: DC magnetron sputtering system.
[0090] Target material: High-purity iron target (99.99%).
[0091] The depositional parameters are shown in Table 2.
[0092] Table 2 Parameters for depositing the second transition layer in Example 2
[0093] Annealing treatment: Silicon carbide material with a deposited iron thin film of vertical columnar crystal structure is placed in a vacuum annealing furnace and annealed at 5.0 × 10⁻⁶. -1 Annealing at 600℃ for 30 min and then furnace-cooled to room temperature yields silicon carbide material with an intermediate layer (columnar porous iron film / silicon-rich layer / textured SiC matrix).
[0094] The surface of the obtained iron thin film with a vertical columnar crystal structure was observed by SEM, and the results are as follows: Figure 3 As shown, Figure 3 The film surface exhibits clear, columnar crystals perpendicular to the substrate, with grain diameters ranging from approximately 100 to 500 nm. Winding channels extend from the substrate to the film surface between the columns. The surface morphology displays a typical "cauliflower-like" porous structure.
[0095] 3. Assembly and reaction sintering welding: 3.1 Assembly: Two prepared SSiC specimens (each with a silicon-rich layer and a vertical columnar crystal structure iron film sequentially prepared on the surface to be welded) were butt-assembled by contacting each other using a method where the iron films with vertical columnar crystal structures are in contact with each other, ensuring that the iron films are in contact with each other. A slight constant pressure of about 0.1 MPa was applied to maintain interfacial contact without crushing the porous membrane.
[0096] 3.2 In Figure 1 Heat treatment in the laser welding gun: Protective gas: Ultra-high purity argon (Ar, 99.999%), flow rate 18 L / min.
[0097] Horizontal blowing gas: Ultra-high purity argon gas with a flow rate of 10 L / min, used to disperse any small amount of volatiles that may be generated.
[0098] Heating method: Focused infrared lamp radiation heating is used, which results in stable temperature rise and low thermal stress.
[0099] Heat treatment process (complete five stages): Phase 1: Heat to 500℃ at 30℃ / min and hold for 10min. During this phase, use high-flow-rate nitrogen to completely purge the air from hollow cavity 2 and annular cavity 3. After the first holding period, turn on the protective gas (high-purity argon, 99.999%) and the cross-blowing gas (high-purity argon, 99.999%), and control the flow rates at 18L / min and 10L / min respectively.
[0100] The second stage (silicon infiltration and initial reaction): The heating power was increased, raising the temperature from 500℃ to the first-stage reaction temperature of 1150℃ at a heating rate of 150℃ / min. This temperature was then held at 1150℃ for 20 minutes. During this process, the flow rates of the protective gas (high-purity argon) and the cross-blowing gas (high-purity argon) were 18 L / min and 10 L / min, respectively. This stage is crucial: the amorphous silicon layer softens and undergoes surface diffusion, rapidly infiltrating into the vertical channels of the iron film through capillary action, achieving uniform nanoscale mixing of iron and silicon in three-dimensional space. Upon contact with silicon, a vigorous exothermic reaction occurs, primarily generating high-silicon-content η-Fe5Si3 and ε-FeSi phases. The porous structure effectively accommodates the volume changes in the initial stage of the reaction.
[0101] The third stage (β-phase formation and densification): The temperature is lowered from 1150℃ to 920℃ at a rate of 20℃ / min, and held at this temperature for 45 min. During this process, the flow rates of the protective gas (high-purity argon) and the cross-blowing gas (high-purity argon) are 18 L / min and 10 L / min, respectively. Solid-state phase transformations such as eutectoid decomposition occur in this stage, ultimately forming a composite bonding layer with β-FeSi2 as the main phase and containing a small amount of residual SiC particles. The long holding time promotes pore closure, achieving high densification of the bonding layer.
[0102] Fourth stage: Turn off the heater and cool down from 920℃ to 400℃ at a rate of 30℃ / min.
[0103] Fifth stage: The protective gas and cross-blowing gas are then turned off, and the mixture is allowed to cool naturally to room temperature. The fifth stage aims to minimize the residual stress caused by the difference in CTE between SiC and β-FeSi2.
[0104] 4. Results and Performance Characterization: Microstructure analysis: Figure 4 SEM image of the cross-section of the welded joint. Figure 4 The interface layer exhibits a uniform thickness of approximately 15 μm. It contains no continuous pores and is composed of equiaxed β-FeSi2 grains with dimensions ranging from 3 to 10 μm, with clear grain boundaries. At the interface between the interface layer and the SiC matrix, a transition zone of approximately 2–3 μm thickness is visible, in which β-FeSi2 grains are interlocked with the SiC matrix, forming a metallurgical and diffusion-mixed bond. The interface is free of cracks or gaps.
[0105] Figure 5 The XRD pattern of the welded joint. Figure 5 The results show that the main phase of the connecting layer is β-FeSi2, accompanied by trace amounts of unreacted SiC diffraction peaks. No residual Fe or brittle phases of high-silicon iron silicides were observed, indicating that the reaction was complete.
[0106] The room temperature three-point bending strength test of the welded joint, conducted according to GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", showed that the joint strength was 475 MPa, reaching 95% of the strength of the base material, and the fracture occurred in the base material rather than the weld.
[0107] After oxidizing in air at 1000℃ for 100 hours, the strength retention rate of the welded joint is >90%.
[0108] Example 3 The difference from Example 2 is that the second transition layer is an iron thin film with an open porous structure, and the preparation parameters are as follows: the working pressure of the magnetron sputtering of the second transition layer is adjusted to 2.0 Pa, and the substrate temperature is adjusted to 50°C. Other operations are the same as in Example 2.
[0109] The surface of the obtained iron thin film with an open porous structure was observed by SEM, and the results are as follows: Figure 6 , Figure 6 The results show that the iron thin film has a distinct open porous structure with interconnected pores, and the pore size is approximately 50~200nm.
[0110] The welded joint has a dense bonding layer, good interface adhesion, and no cracks.
[0111] XRD pattern of welded joint and Figure 5 They are basically the same, with the main phase being β-FeSi2 and no other impurities.
[0112] The room temperature three-point bending strength test of the welded joint, conducted according to GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", showed that the joint strength was 450 MPa, reaching 90% of the strength of the base material, and the fracture occurred in the base material rather than the weld.
[0113] After oxidizing in air at 1000℃ for 100 hours, the strength retention rate of the welded joint is >85%.
[0114] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A welding method for silicon carbide materials, characterized in that, Includes the following steps: The surface of the silicon carbide material to be welded is pretreated to obtain pretreated silicon carbide material; The free silicon content of the silicon carbide material is greater than or equal to 10 wt%; A transition layer is applied to the surface of the pretreated silicon carbide material to be welded, and then annealing is performed to obtain silicon carbide material with an intermediate layer attached. After assembling the silicon carbide material with the intermediate layer attached in a contact manner, heat treatment is performed to achieve welding of the silicon carbide material; The transition layer is either a first transition layer or a second transition layer; The first transition layer is a periodically stacked silicon-iron layer, which is a stacked silicon layer and an iron layer, and the iron layer is in contact with the silicon carbide material; The second transition layer is an iron thin film, which has an open porous structure or a vertical columnar crystal structure.
2. The welding method for silicon carbide material according to claim 1, characterized in that, When the free silicon content of the silicon carbide material is less than 10 wt%, the method further includes: applying a silicon-rich layer to the surface of the pretreated silicon carbide material to be welded, and then applying a transition layer. The silicon-rich layer is a polycrystalline Si layer, an amorphous silicon layer, or a Si-SiC hybrid layer; the free silicon content in the silicon-rich layer is greater than or equal to 90 wt%. The thickness of the silicon-rich layer is 5~50μm.
3. The welding method for silicon carbide material according to claim 1, characterized in that, The total thickness of the first transition layer is 0.4~2μm. In the first transition layer, the thickness of the single silicon layer is 5~8nm and the thickness of the single iron layer is 4~8nm; the thickness of the single silicon layer is greater than the thickness of the single iron layer.
4. The welding method for silicon carbide material according to claim 3, characterized in that, The single-layer silicon layer is applied by magnetron sputtering, and the magnetron sputtering parameters of the single-layer silicon layer include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working gas pressure is 0.5~1.0Pa, sputtering power is 150~400W, substrate temperature is 200~400℃, deposition time is 15~90s, target-substrate distance is 60~100mm; The single-layer iron layer is applied by magnetron sputtering, and the magnetron sputtering parameters of the single-layer iron layer include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working gas pressure is 0.3~0.8Pa, sputtering power is 100~300W, substrate temperature is 200~400℃, deposition time is 5~60s, target-substrate distance is 60~100mm.
5. The welding method for silicon carbide material according to claim 1, characterized in that, The total thickness of the second transition layer is 5~100μm; The second transition layer is applied by magnetron sputtering; When the second transition layer is an iron thin film with an open porous structure, the magnetron sputtering parameters include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working gas pressure is 1.0~2.5Pa, sputtering power is 80~200W, substrate bias voltage is 0V or -20~-50V, substrate temperature is 25~100℃, deposition rate is 0.5~2nm / s, target-substrate distance is 60~100mm. When the second transition layer is an iron thin film with a vertical columnar crystal structure, the magnetron sputtering parameters include: The background vacuum level is less than or equal to 5.0 × 10⁻⁶. -4 Pa, working gas is argon, working pressure is 3.0~5.0Pa, sputtering power is 80~200W, substrate bias is 0V or -20~-50V, substrate temperature is 25~100℃, deposition rate is 0.5~2nm / s, target-substrate distance is 60~100mm.
6. The welding method for silicon carbide material according to claim 1, characterized in that, The annealing treatment is performed at a temperature of 500~700℃, with a holding time of 15~60 min, and the vacuum degree of the annealing treatment is 1×10⁻⁶. -1 ~9×10 -1 Pa.
7. The welding method for silicon carbide material according to claim 1, characterized in that, The heating process of the heat treatment includes sequentially performing a first stage, a second stage, a third stage, and a fourth stage. The first stage is: heating to a first temperature at a first heating rate and then holding for a first time; The first stage is carried out under the condition of introducing protective gas; The second stage is: heating from the first temperature to the second temperature at a second heating rate and then holding for a second time; The third stage is: cooling down from the second temperature to the third temperature at a first cooling rate and then holding the temperature for the third time. The fourth stage is: cooling from the third temperature to the fourth temperature at a second cooling rate; The atmosphere in the second and third stages is a protective gas.
8. The welding method for silicon carbide material according to claim 7, characterized in that, The first heating rate is 25~35℃ / min, the first temperature is 500~600℃, and the first holding time is 2~10min; The second heating rate is 100~300℃ / min, the second temperature is 1130~1170℃, and the second holding time is 10~30min; The first cooling rate is 15~20℃ / min, the third temperature is 910~930℃, and the third holding time is 30~60min; The second cooling rate is less than or equal to 50℃ / min, and the fourth temperature is 300~400℃.
9. The welding method for silicon carbide material according to claim 1, characterized in that, The pretreatment includes machining.
10. The welding method for silicon carbide material according to claim 1, characterized in that, When the size of the silicon carbide material is greater than 1m, the heat treatment is performed in a laser welding gun, which includes: Welding torch body: The welding torch body has a hollow cavity (2), which is used to introduce shielding gas; the hollow cavity (2) is surrounded by an annular cavity (3), which is used to introduce cross-blowing gas; the hollow cavity (2) is surrounded by a water cooling jacket (4). Flexible sealing skirt (1), the flexible sealing skirt (1) is connected to the head of the welding gun body; A multi-channel gas supply system, comprising a protective gas supply system, a cross-blowing gas supply system and a displacement gas supply system; the protective gas supply system is connected to the hollow cavity (2), the cross-blowing gas supply system is connected to the annular cavity (3), and the displacement gas supply system is connected to both the hollow cavity (2) and the annular cavity (3).